Condiciones de infraestructura y equipamiento de los hoteles de cuatro y cinco estrellas de la provincia de Trujillo para la atención del segmento personas con discapacidad, 2015. - Avalos Pumaricra, Katheryne Esther (2017)
This thesis report entitled "Infrastructure conditions and equipment of the four and five star hotels of the province of Trujillo for the attention of the segment of people with disabilities, 2015", aims to determine the infrastructure and equipment conditions of the Hotels of four and five stars, which after having been evaluated and / or diagnosed the state in which they are currently, check the optimal conditions that these hotels have for the attention of the segment of people with disabilities, as well The interview was carried out to the entrepreneurs in charge of hotel administration, proving the commitment and responsibility for conditioning their establishment; Thus achieving a wider reach of what social inclusion means and the importance of this for inclusive tourism, seeking to integrate the disabled person into all types of tourism activities._x000D_ The methodological approach of the present investigation was based on the descriptive method, since the conditions that the hotels of four and five stars were presented, as well as the use of the techniques of direct observation, the interview and the signing, besides Instruments were applied such as the field book, observation sheet, interview questionnaire, camera and recorder.